Demanding innovation in technology for economic development - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
There is a clamour of increasing intensity among today´s young generation in Africa, and probably in all ACP regions, about the lack of discernible industrial and economic development in their countries. Professor Chetsanga argues in this contributi